Psychological Impacts of Teaching Models on Ibero-American Educators during COVID-19 - Simone Nomie Sato; Emilia Condes Moreno; Adriana Rico Villanueva; Paulo Orquera Miranda; Pascual Chiarella; Gloria Bermudez; Jose Francisco Tornero Aguilera; Vicente Javier Clemente-Suárez (Behavioral Sciences, 2023)
Educational systems globally, and notably in the Ibero-American context, underwent significant adaptations in response to the myriad challenges imposed by the COVID-19 pandemic. The pedagogical evolution unfolded through three discernible phases: predominantly online, hybrid, and ultimately, a return to face-to-face instruction. While these phases were universally apparent, cultural, socio-economic, and health disparities across regions subtly influenced the quality and experiential aspects of teaching and learning within these models. This study seeks to illuminate the psychological profiles and evaluative perspectives regarding teaching and learning quality among university educators during COVID-19’s tri-phase educational transformation. Engaging 601 university instructors from various Ibero-American countries, a comprehensive questionnaire mapped demographic, academic, and psychological landscapes across the pandemic’s distinctive epochs. The pivot to online educational methodologies, supplanting traditional modalities, permeated numerous facets of the educational endeavor, particularly impacting faculty life and wellbeing. Data underscored a prevalent sentiment of loneliness, indicative of broader mental health challenges, especially pronounced among educators in Latin American nations. Notwithstanding these hurdles, Latin American educators demonstrated a predilection towards online instruction, in stark contrast to their European peers, who exhibited a preference for in-person pedagogy. This study unveils the divergent pedagogical preferences and mental health challenges among university educators in the Ibero-American realm during COVID-19’s educational shifts, underlining the need for adaptable educational frameworks and robust mental health support, attuned to the region’s distinct socio-cultural and economic contexts.